Examining the Volatility of Conventional Cryptocurrencies and Sustainable Cryptocurrency during Covid-19: Based on Energy Consumption - Anandhabalaji, V.; Babu, Manivannan; Gayathri, J.; Sathya, J.; Indhumathi, G.; Brintha, R.; Michael, Justin Nelson (International Journal of Energy Economics and Policy, 2023)
The present study proposes to investigate the influence of the covid-19, on the adjusted closing price of the digital currency based on energy consumption during the process of mining. The study employed the secondary data analysis of top ten market capitalization of cryptocurrencies with the combination of high energy consume mechanism (proof of work) and low energy consume mechanism (proof of stake). Statistical tools like Descriptive analysis,Augmented Dickey-Fuller (ADF) test, ARCH, and GARCH models were used in the study. The present study finds that the prices of cryptocurrencies were highly volatile. This study could assist investors towards better understanding of the dynamics of the cryptocurrency market based on energy consumption which helps them to make more effective decisions, on investing cryptocurrencies with a scientific approach.